ANALISIS HAMBATAN TERHADAP VARIASI BENTUK DAN SUDUT NACA AIRFOIL SEBAGAI SELF MANEUVERING PADA UNMANNED SURFACE VEHICLE (USV) - Saiful Fadillah (2023)
Unmanned Surface Vehicle (USV) can be used as the right choice as a measurement tool for ocean data such as wave recording, hydrographic data, oceanographic data, and other ocean data measurements compared to using large research ships and using large costs. Therefore the latest design with NACA AIRFOIL as three forms of the ship's body uses a self-maneuvering system on the USV which is able to provide a smaller resistance value so that it has long durability is needed. This thesis will discuss the pressure of the fluid flow and how to analyze distance wave interference between NACA AIRFOIL as three ship hull shapes as well as self-maneuvering on (USV) to show the significance of the effect on decreasing and increasing drag using the Computational Fluid Dynamics (CFD) analysis on ansys CFX. Based on the results of the simulations that have been carried out on each model variation from variation one to variation eight, the best USV model configuration to reduce resistance is variation seven, namely the NACA 0024 type with two NACA positions behind without using the NACA angle of attack and one NACA in front. with the lowest resistance value at a speed of 0.2 m/s which has a resistance value of 0.47 N.